Characteristic and Pregnancy Rate of IVF Patient: a Retrospective Analysis from Two Centres - Lestari, Linda; Pratama, Gita; Maidarti, Mila; K. Harzif, Achmad; Wiweko, Budi (KnE Medicine, 2016)
Introduction: According to recent statistics, infertility in Indonesia reached 21,9%. In-vitro fertilization (IVF) was a reliable treatment option for subfertility couples with success rate of 22-40%. Data from the Indonesia Association for In-Vitro Fertilization (Perfitri) in 2010 showed the country had only 2000 cases, one third of Vietnam’s and half of Thailand’s. The technology’s high cost has been cited as the cause behind the slow development of IVF in Indonesia. Objective: We aim to evaluate the characteristics of patients and their pregnancy rate following in vitro fertilization in infertile couples from two different centres, Yasmin Clinic and Kedoya Clinic. Material and methods: Cohort retrospective was used to analyse outpatient data from two fertility centres. A total of 510 outpatients’ data, 405 in Yasmin Clinic and 105 in Kedoya Clinic, between October 2014 to September 2015 was collected. Patients and in vitro fertilization cycle characteristics from both clinics were evaluated. The pregnancy rate after IVF was compared between the groups. Result: Although maternal age (p=0,032) and paternal age (p=0,017) were statistically significant, they were not clinically significant. There were also no significant differences in the characteristics of in vitro fertilization in both clinics, clinically. However, pregnancy rate was higher in Yasmin Clinic than in Kedoya Clinic, with pregnancy rate of 64,8% and 45,7%, respectively (OR = 2,185; 95%CI 1,420-3,361; p=0,001). Discussion: There were no differences between characteristics of patients and in vitro fertilization cycle in both centres. Nevertheless, pregnancy rate between Yasmin Clinic and Kedoya Clinic were statistically different, suggesting another factors that influence success rate of in vitro fertilization. This research showed that most patients seek medical attention at the age of 35, after 7 years of infertility, suggesting awareness of infertility problem is still low.